Machine Learning for Physics Applications: Quantum Algorithm Design, Chaotic Dynamics, and Mass Spectrometry - Rouillard, Amy Shirley (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.